Inactivation of Listeria innocua on packaged meat products by pulsed light. (September 2019) - Kramer, B.; Wunderlich, J.; Muranyi, P.
Highlights: Pulsed light treatments reduced Listeria innocua on packaged ham by 1 log. Pulsed light treatments reduced Listeria innocua on packaged frankfurter sausages by 3–4 log. Reduction level of Listeria innocua was maintained during storage. Intense treatments induced off-odor. Abstract: Contaminations of food with Listeria monocytogenes pose a serious threat to human health, especially in case of chilled ready-to-eat products. Pulsed Light (PL) represents a promising technology to reduce microorganisms, including pathogens, on food surfaces. The application of intense light flashes of a broad spectrum (200–1100 nm) has been approved by the FDA in 1996 for food disinfection at a maximum fluence of 12 J/cm². Its mode of microbial inactivation is mainly attributable to DNA alterations as a result of UV-light exposure. In this study, the applicability of PL for disinfection of packaged frankfurter sausages (two different casings), sliced boiled ham and chicken cold cuts was investigated. Artificially inoculated product samples were packaged in PA/PE vacuum bags and subsequently PL treated (0.35 J/cm²–3.6 J/cm²) in order to assess the inactivation efficiency as well as the impact on the food quality. It was shown that PL treatments allow reductions of L. innocua by about 1 log on the surface of sliced boiled ham and chicken cold cuts while 3–4 log can be achieved on frankfurter sausages. The initial count reduction was maintained over 12 days of chilled storage (5 °C) and no impact on product color and appearance was observed. However, exposure to high PL doses induced significant sensory deviations which were identified by triangle tests. This study shows that moderate PL treatments, which provide distinct count reduction of pathogens while not affecting the product quality, can be a viable measure to increase food safety of packaged meat products.